2019
DOI: 10.1177/0300060519874154
|View full text |Cite
|
Sign up to set email alerts
|

Repeated reverse sural fasciocutaneous flap is an effective surgical strategy for repairing long segmental soft tissue defects of the tibia

Abstract: ObjectiveThis study was performed to introduce our surgical strategy and experience in applying a repeated reverse sural fasciocutaneous flap (RSFF) to repair large areas of tibial exposure.MethodsDuring a 3-year period, 10 patients with a large area of tibial exposure and intact posterior skin and soft tissue after trauma were treated in our hospital using a repeated RSFF. First, most of the area of proximal tibial exposure was covered by an RSFF. Three weeks later, another smaller RSFF was designed from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Our results were supported by study of Cui et al [13] as they reported that ten patients were treated with the same surgical plan for wound repair. The patients comprised seven males and three females ranging in age from 18 to 65 years.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our results were supported by study of Cui et al [13] as they reported that ten patients were treated with the same surgical plan for wound repair. The patients comprised seven males and three females ranging in age from 18 to 65 years.…”
Section: Discussionsupporting
confidence: 88%
“…In a study conducted by Cui et al [13] , the duration of tibial exposure ranged from 5 to 20 days [mean, 14 ± 7.3 days]. After reverse sural fasciocutaneous flap [RSFF] surgery, local skin flap necrosis occurred in two patients, and all wounds in the remaining eight patients healed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations